Forklifts - Zuehlke, Jeffrey (Minneapolis : Lerner Publications Co., 2007)
Simple text and color illustrations describe what forklifts do, how they are loaded, and how drivers make them move.
Includes index.
Keywords: Forklift trucks -- Juvenile literature